Design infrastructure: Australian developments - Love, Terence (International Association of Societies of Design Research, 2005)
The paper reports preliminary findings from research into Australia's design infrastructure. Design infrastructure comprises the systems, institutions and expertise that enables design activity to be undertaken. Design activity is an essential aspect of the innovation and knowledge processes central to national and local economic and social development.The research indicated that there exist significant weaknesses in Australia's design infrastructure. By implication and observation, these weaknesses compromise Australian investments in innovation, research, education and business process change.The paper maps out several dimensions of these weaknesses and their causes and implications. It concludes with suggestions for organisational and funding initiatives to improve Australia's design infrastructure in ways that will enable Australia to realise and advance national and local programs for economic and social development.